Ultrahigh-strength carbon material and preparation method thereof

By combining sugar-polyacrylamide hydrogel technology and reinforced particles, the preparation process of graphite bulk carbon materials is simplified, and the existing problems of complex processes, long cycles, high costs and poor mechanical properties are solved, and high strength and low-cost carbon materials are achieved.

CN119797921AActive Publication Date: 2025-04-11HARBIN INST OF TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510014960.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The existing graphite block materials have complex preparation processes, long cycles, high costs, difficult microstructure control and poor mechanical properties.

Method used

Ultra-high strength carbon materials are prepared by combining sugar-polyacrylamide hydrogel technology with reinforced particles, and high-temperature carbonization and graphitization are carried out after molding or isostatic molding.

Benefits of technology

The production process of graphite bulk carbon materials has been significantly simplified, the carbon yield has been improved, the microstructure of the material has been optimized, and key indicators such as bending strength have been improved, reducing production costs and time costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797921A_ABST
    Figure CN119797921A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrahigh-strength carbon material and a preparation method thereof, and belongs to the technical field of carbon materials, and the preparation method comprises the following steps: adding reinforced particles, acrylamide, water-soluble saccharides, N, N '-methylene bisacrylamide, an initiator and a catalyst into deionized water, uniformly mixing, and then sequentially carrying out drying, heat treatment, crushing and ball milling treatment to obtain the ultrahigh-strength carbon material. Composite powder is obtained; the composite powder is sequentially subjected to forming and carbonization treatment, and the ultrahigh-strength carbon material is obtained. By adopting an innovative two-step preparation process, the production process of the graphite block carbon material is remarkably simplified, and the problems of complex process, long production period, high raw material cost, difficulty in controlling the microstructure and the like in the prior art are effectively solved. A strategy of combining a sugar-polyacrylamide hydrogel technology and reinforced particles is utilized, the carbon yield is greatly improved, and carbon loss caused by gas release in a carbonization process is reduced, so that the microstructure of the material is optimized, and the mechanical properties, including key indexes such as compression resistance and bending strength, of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of carbon materials, and in particular relates to an ultra-high-strength carbon material and a preparation method thereof. Background Art

[0002] Carbon (graphite) materials occupy an important position in industrial applications due to their excellent electrical and thermal conductivity, high mechanical strength, low thermal expansion coefficient, high temperature resistance and excellent thermal stability. These characteristics make isotropic graphite widely used in metallurgy, chemical industry, electronics and nuclear industry, especially in high-end anti-friction materials, military industry, aerospace, semiconductor manufacturing, nuclear graphite for high temperature gas-cooled reactors and ultra-high power electrodes. It plays an irreplaceable role in high-tech fields.

[0003] Existing methods for preparing isotropic graphite mainly include traditional methods and self-sintering methods. The traditional method uses petroleum coke, asphalt coke or anthracite as raw materials, grinds them into fine powder as aggregate, adds binders such as coal tar or artificial resin, and isostatically pressed, and then obtains the finished product by high-temperature roasting, repeated impregnation and graphitization. Although this process is mature, it has the problems of long production cycle and complex process, and because the product structure is mostly heterogeneous structure, the isotropy is poor, which limits the improvement of its mechanical properties. The self-sintering method uses powder with self-sintering properties (such as raw petroleum coke powder and mesophase asphalt-based powder, etc.), does not use binders, and prepares graphite materials by high-temperature roasting and graphitization after compression molding. Although this method reduces the use of binders, it has high performance requirements for raw material powders, and usually requires modification, resulting in increased manufacturing costs. In addition, the self-sintering method is prone to problems such as excessive shrinkage and cracks in the finished product during the production process, resulting in a low yield rate and complex process operations.

[0004] Therefore, there is an urgent need to provide a new preparation method to prepare carbon materials with excellent mechanical properties. Summary of the invention

[0005] To solve the problems of complex preparation process, long cycle, high cost, difficult microstructure control and poor mechanical properties of existing graphite block materials. The present invention proposes an ultra-high strength carbon material and its preparation method, that is, the sugar-polyacrylamide hydrogel technology and the introduction of reinforcing particles are used, combined with the process of high-temperature carbonization and graphitization after molding or isostatic pressing to prepare ultra-high strength carbon materials, wherein the sugar-polyacrylamide hydrogel method can significantly improve the carbon yield and effectively reduce the carbon loss of sugar during the heat treatment process, while the addition of reinforcing particles helps to optimize the microstructure of the material and improve the mechanical properties of the material. This method not only significantly shortens the preparation cycle and reduces production costs, but also solves the bottleneck of traditional methods in microstructure design, successfully prepares high-strength and dense carbon (graphite) materials, and provides technical support for its further promotion in industrial applications, and is particularly suitable for the development of high-strength and low-cost carbon materials.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention:

[0008] A method for preparing an ultra-high-strength carbon material comprises the following steps:

[0009] The reinforcing particles, acrylamide, water-soluble sugar, N,N'-methylenebisacrylamide, initiator and catalyst are added into deionized water and mixed evenly, and then dried, heat treated, crushed and ball milled in sequence to obtain composite powder of the reinforcing particles wrapped with sugar-polyacrylamide hydrogel (binder);

[0010] The composite powder is formed and then carbonized to prepare the ultra-high strength carbon material.

[0011] Preferably, taking the sum of the weight percentages of the acrylamide, water-soluble sugar, N,N'-methylenebisacrylamide and deionized water as 100%, the acrylamide: water-soluble sugar: N,N'-methylenebisacrylamide = 1-30%: 5-60%: 0.05-3%, and the balance is water.

[0012] Preferably, the added amount of the reinforcing particles is 20% to 300% of the sum of the weight of the acrylamide, the water-soluble sugar, the N,N'-methylenebisacrylamide and the deionized water.

[0013] Preferably, the preparation process of the reinforced particles is:

[0014] acrylamide, water-soluble sugar and N,N'-methylenebisacrylamide are mixed and dissolved in deionized water, and stirred to form a uniform solution; then the solution is gelled at 50-200°C and dried to obtain a hydrogel;

[0015] heat-treating the hydrogel in a muffle furnace to obtain a pretreated product;

[0016] Carrying out carbonization treatment on the pretreated product under inert atmosphere (vacuum or argon or nitrogen) to obtain a carbonized product;

[0017] The carbonized product is pulverized and then ball-milled in a ball mill to obtain carbonized powder (reinforced particles).

[0018] More preferably, in terms of weight percentage, the acrylamide: water-soluble sugar: N,N'-methylenebisacrylamide = (1-30%): (5-60%): (0.05-3%), and the balance is deionized water.

[0019] More preferably, in terms of weight percentage, the ratio of acrylamide: water-soluble sugar: N,N'-methylenebisacrylamide = 7.39%: 24.65%: 0.18%.

[0020] More preferably, the water-soluble sugars include one or more of glucose, fructose, galactose, maltose, sucrose, lactose or oligofructose.

[0021] More preferably, the conditions during the heat treatment are:

[0022] The temperature is raised to 140-350°C at a heating rate of 0.1-20°C / min, and then kept at this temperature for 0.5-30h; wherein the heating mode is direct heating or step-by-step heating.

[0023] More preferably, the conditions during the carbonization process are:

[0024] The temperature is raised to 500-1600°C at a heating rate of 1-20°C / min, and then kept at this temperature for 0.5-30h; wherein the heating mode is direct heating or step-by-step heating.

[0025] More preferably, the conditions during the ball milling process are:

[0026] The ball-to-material ratio is 1-20:1, the ball mill speed is 100-600r / min, and the ball mill time is 6-48h.

[0027] Preferably, the initiator is a 10% by mass aqueous solution of ammonium persulfate, and the amount thereof added is 0.5% to 3% of the total mass of acrylamide, water-soluble sugars, N,N'-methylenebisacrylamide and deionized water; and / or

[0028] The catalyst is a triethanolamine aqueous solution with a mass fraction of 10%, and the added amount thereof is 0.5%-3% of the total mass of acrylamide, water-soluble sugars, N,N'-methylenebisacrylamide and deionized water.

[0029] Preferably, the forming is performed by compression molding or isostatic pressing.

[0030] Preferably, the conditions during the molding process are:

[0031] The process is carried out under the conditions of a pressure of 10-600 MPa and a temperature of 120-900° C. and is kept warm for 0.5-6 hours to obtain a block-shaped green body.

[0032] Preferably, the conditions of the carbonization process are:

[0033] In an inert atmosphere, the temperature is increased to 1000-3000°C at a heating rate of 1-20°C / min, and then kept at this temperature for 0.5-24 hours; wherein the heating mode is direct heating or step-by-step heating.

[0034] More preferably, during the carbonization process:

[0035] When the temperature is raised to 1000-1600°C, a high-strength isotropic nanocrystalline / amorphous carbon bulk carbon material is obtained;

[0036] When the temperature is raised to 1800-2400°C, a high-strength isotropic three-dimensional network graphene / amorphous carbon block carbon material is obtained;

[0037] When the temperature is raised to 2600-3000°C, a high-strength isotropic graphite material is obtained.

[0038] The second technical solution of the present invention:

[0039] The ultra-high strength carbon material prepared by the above preparation method.

[0040] Compared with the prior art, the present invention has the following advantages and technical effects:

[0041] The present invention significantly simplifies the production process of graphite block carbon materials by adopting an innovative two-step preparation process, and effectively overcomes the problems of complex process, long production cycle, high raw material cost and difficult control of microstructure in the prior art. The strategy of combining sugar-polyacrylamide hydrogel technology with reinforcing particles greatly improves the carbon yield, reduces the carbon loss caused by gas release during carbonization, thereby optimizing the microstructure of the material and improving its key indicators such as bending strength. At the same time, the simplified process of the method significantly reduces the production cost and time cost, and improves the feasibility and economic benefits of industrial production. The prepared high-strength carbon material shows significant application prospects in high-tech fields such as aerospace, electronics, and metallurgy, which not only promotes the technological development of graphite-based materials, but also provides a practical solution for the development of a new generation of high-performance carbon materials. Therefore, a method for preparing an ultra-high-strength carbon material provided by the present invention will bring obvious social benefits and meet the growing market demand for high-strength, low-cost carbon materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0043] Figure 1 The microstructure diagram of the nanocrystalline / amorphous carbon bulk carbon material obtained in Example 1;

[0044] Figure 2 The microstructure diagram of the three-dimensional network graphene / amorphous carbon composite material obtained in Example 2;

[0045] Figure 3 The microstructure diagram of the graphite bulk carbon material obtained in Example 3;

[0046] Figure 4 This is a bending strength curve diagram of the carbon material prepared in Examples 1-3. DETAILED DESCRIPTION

[0047] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0048] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0049] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0050] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0051] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0052] The present invention selects acrylamide and water-soluble sugar substances as starting materials and adopts a two-step method to prepare ultra-high-strength carbon (graphite) materials. The first step is to prepare reinforcing particles; the second step is to use the reinforcing particles as aggregates and sugar-polyacrylamide hydrogel as a binder to prepare ultra-high-strength carbon (graphite) materials. The preparation process of ultra-high-strength carbon materials is as follows:

[0053] The first step is to prepare reinforced particles:

[0054] Acrylamide, water-soluble sugars, and N,N'-methylenebisacrylamide are weighed in weight proportions of 1-30%, 5-60%, and 0.05-3%, respectively, and deionized water is added as the remainder. The amount of deionized water can be adjusted according to specific needs to control the relative proportions of other raw materials in the system.

[0055] The sample preparation process is as follows: First, acrylamide, water-soluble sugars and N, N'-methylenebisacrylamide are mixed and dissolved in deionized water and stirred to form a uniform solution. The solution is then gelled and dried at 50-200°C to obtain a hydrogel. The hydrogel is then heat-treated in a muffle furnace at 140-350°C, with a heating rate of 0.1-20°C / min, a heating mode of direct heating or step-by-step heating, and a pretreatment product is obtained after the target temperature is reached. The pretreatment product is further carbonized under vacuum / argon / nitrogen conditions, with a heating rate of 1-20°C / min, a heating mode of direct heating or step-by-step heating, and a carbonization product is obtained after the target temperature is reached at 500-1600°C. The carbonized product is crushed and then ball-milled in a ball mill with a ball-to-material ratio of 1 to 20:1, a ball-milling speed of 100 to 600 r / min, and a ball-milling time of 6 to 48 h. Carbonized powder is obtained after ball milling, and the carbonized powder is used as the reinforcing particles in the second step.

[0056] Step 2: Use the reinforced particles as aggregate and sugar-polyacrylamide hydrogel as binder to prepare ultra-high strength carbon (graphite) material:

[0057] First, prepare a sufficient amount of initiator (aqueous solution of ammonium persulfate with a mass concentration of 10%) and catalyst (aqueous solution of triethanolamine with a mass concentration of 10%) for standby use. Then weigh acrylamide, water-soluble sugars, and N,N'-methylenebisacrylamide in weight proportions of 1-30%, 5-60%, and 0.05-3%, respectively, and add deionized water to make up to 100%. Among them, the amount of deionized water can be adjusted according to specific needs to control the relative proportion of other raw materials in the system. The amount of enhanced particles added accounts for 20% to 300% of the mass of the above solution.

[0058] Secondly, acrylamide, water-soluble sugar, N,N'-methylenebisacrylamide, and reinforcing phase particles are mixed in deionized water, and 0.5% to 3% of the total mass of the solution is added with an initiator, and stirred to form a uniformly dispersed solution. Then, 0.5% to 3% of the total mass of the solution is added with a catalyst, so that the solution quickly gels.

[0059] The obtained gel is transferred to a blast oven and dried at 60-200°C for 12-48 hours to remove free water. The hydrogel is then heat-treated in a muffle furnace at 120-350°C, with a heating rate of 0.1-20°C / min, and a heating mode of direct heating or step-by-step heating. After reaching the target temperature, it is kept warm for 0.5-30 hours to obtain a pretreated product. After the pretreated product is crushed, it is ball-milled in a ball mill with a ball-to-material ratio of 1-20:1, a ball milling speed of 100-600r / min, and a ball milling time of 6-48 hours. After ball milling, a composite powder of binder-wrapped reinforcing particles is obtained.

[0060] The composite powder is kept warm at a pressure of 10 to 600 MPa and a temperature of 120 to 900° C. for 0.5 to 6 hours to obtain a block-shaped green body.

[0061] The green body obtained above is subjected to carbonization treatment under vacuum / N2 / Ar or other protective atmosphere conditions, with a heating rate of 1-20°C / min, a heating mode of direct heating or step-wise heating, a target temperature of 1000-1600°C, and a holding time of 0.5-6h to obtain a high-strength isotropic nanocrystalline / amorphous carbon bulk carbon material; and / or

[0062] The green body obtained above is subjected to carbonization treatment under protective atmosphere conditions such as vacuum / N2 / Ar, with a heating rate of 1 to 20°C / min, a heating mode of direct heating or step-wise heating, a target temperature of 1800 to 2400°C, and a holding time of 0.5 to 6h to obtain a high-strength isotropic three-dimensional network graphene / amorphous carbon block carbon material; and / or

[0063] The green body obtained above is carbonized under protective atmosphere conditions such as vacuum / N2 / Ar, with a heating rate of 1-20°C / min, a heating mode of direct heating or step-by-step heating, a target temperature of 2600-3000°C, and a holding time of 0.5-6h to obtain a high-strength isotropic graphite material.

[0064] In some preferred embodiments, the water-soluble sugars include one or more of glucose, fructose, galactose, maltose, sucrose, and lactose.

[0065] In some preferred embodiments, in the first step, acrylamide, water-soluble sugars, and N,N'-methylenebisacrylamide are 7.39%, 24.65%, and 0.18% by weight, respectively; the remainder is deionized water.

[0066] In some preferred embodiments, the preparation process of the ultra-high strength carbon material is:

[0067] The first step is to prepare the reinforced particles:

[0068] Acrylamide, water-soluble sugars, and N, N'-methylenebisacrylamide were weighed in weight proportions of 7.39%, 24.65%, and 0.18%, respectively, and deionized water was added as the remainder, with a weight proportion of 67.78%. Among them, the amount of deionized water can be adjusted according to specific needs to control the relative proportion of other raw materials in the system. The sample preparation process is as follows: First, acrylamide, water-soluble sugars and N, N'-methylenebisacrylamide are mixed and dissolved in deionized water and stirred to form a uniform solution. The solution is then gelled and dried at 80°C to obtain a hydrogel. The hydrogel is then heat-treated in a muffle furnace at 220°C, with a heating rate of 0.5°C / min, a heating mode of direct heating or step-by-step heating, and the temperature is kept for 2 hours after reaching the target temperature, and then the pretreated product is obtained and recorded as PG-220. The PG-220 sample was further carbonized under vacuum / argon / nitrogen conditions, with a heating rate of 4°C / min, and the heating mode was direct heating or step-by-step heating. After reaching the target temperature of 1100°C, it was kept for 2 hours, and the obtained carbonized product was recorded as PG-1100. After all samples were crushed, they were ball milled in a ball mill with a ball-to-material ratio of 3:1, a ball milling speed of 200r / min, and a ball milling time of 16 hours. After ball milling, carbonized powder was obtained, which was used as the reinforcing particles in the second step.

[0069] The second step is to prepare ultra-high strength carbon (graphite) materials using reinforced particles as aggregate and sugar-polyacrylamide hydrogel as binder:

[0070] First, sufficient amounts of an initiator (a 10% by mass aqueous solution of ammonium persulfate) and a catalyst (a 10% by mass aqueous solution of triethanolamine) were prepared for use.

[0071] Then, acrylamide, water-soluble sugar, and N,N'-methylenebisacrylamide are weighed in weight proportions of 7.39%, 24.65%, and 0.18%, respectively, and deionized water is added as the remainder. The amount of deionized water can be adjusted according to specific needs to control the relative proportions of other raw materials in the system. The amount of enhanced particles added accounts for 50% of the mass of the above solution.

[0072] The sample preparation process is as follows: First, acrylamide, water-soluble sugars, N,N'-methylenebisacrylamide, and reinforcing phase particles are mixed and dissolved in deionized water, and 1% of the total mass of the solution (a 10% mass fraction of ammonium persulfate aqueous solution) is dripped, and stirred to form a uniformly dispersed solution. Then, 1% of the total mass of the solution (a 10% mass fraction of triethanolamine aqueous solution) is dripped to make the solution gel quickly.

[0073] The obtained gel was transferred to a blast oven and dried at 120°C for 24 hours to remove free water. The hydrogel was then heat treated in a muffle furnace at 220°C, with a heating rate of 0.5°C / min, and the heating mode was direct heating or step-by-step heating. After reaching the target temperature, it was kept warm for 2 hours, and then the pretreated product was obtained and recorded as PG-220. After the pretreated sample was crushed, it was ball milled in a ball mill with a ball-to-material ratio of 3:1, a ball milling speed of 200r / min, and a ball milling time of 16 hours. After ball milling, a composite powder of binder-wrapped reinforced particles was obtained.

[0074] The composite powder is kept at a pressure of 200 MPa and a temperature of 500° C. for 2 hours to obtain a block-shaped green body.

[0075] 1. The green body obtained above is carbonized under vacuum / N2 / Ar protective atmosphere conditions, with a heating rate of 4°C / min, a heating mode of direct heating or step-by-step heating, a target temperature of 1100°C, and a holding time of 2h to obtain a high-strength isotropic nanocrystalline / amorphous carbon bulk carbon material.

[0076] 2. The green body obtained above is carbonized under protective atmosphere conditions such as vacuum / N2 / Ar, with a heating rate of 4°C / min, a heating mode of direct heating or step-by-step heating, a target temperature of 2400°C, and a holding time of 2h to obtain a high-strength isotropic three-dimensional network graphene / amorphous carbon block carbon material.

[0077] 3. The green body obtained above is carbonized under protective atmosphere conditions such as vacuum / N2 / Ar, with a heating rate of 4°C / min, a heating mode of direct heating or step-by-step heating, a target temperature of 2800°C, and a holding time of 2h to obtain a high-strength isotropic graphite material.

[0078] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.

[0079] The "parts" described in the present invention, unless otherwise specified, refer to parts by mass.

[0080] The raw materials used in the present invention are all purchased from the market.

[0081] The technical solution of the present invention is further illustrated by the following embodiments.

[0082] Example 1

[0083] The ultra-high strength carbon (graphite) material is prepared by a two-step method, and the specific process is as follows:

[0084] (1) Preparation of reinforced particles:

[0085] Take 73.9g of acrylamide, 246.5g of glucose and 1.8g of N,N'-methylenebisacrylamide, and 677.8mL of deionized water. Dissolve all raw materials in deionized water and stir until a uniform and transparent solution state. The solution was gelled at 80°C and dried for 24 hours to obtain a hydrogel. Subsequently, the hydrogel was heated to 220°C in a muffle furnace at a heating rate of 0.5°C / min, and the pretreated product PG-220 was obtained after 2 hours of insulation. The PG-220 sample was heated to 1100°C at 4°C / min in an argon environment and kept warm for 2 hours to obtain a carbonized product PG-1100. The PG-1100 sample was crushed and ball-milled in a ball mill at a ball-to-material ratio of 3:1 and a speed of 200r / min for 16 hours to obtain a reinforced particle carbonized powder.

[0086] (2) Preparation of ultra-high strength carbon (graphite) materials:

[0087] Prepare sufficient amounts of initiator (10% ammonium persulfate aqueous solution) and catalyst (10% triethanolamine aqueous solution) for use. Take 6g acrylamide, 20g glucose and 0.15g N,N'-methylenebisacrylamide, 1.5mL initiator, 41g reinforcing particles, and 55mL deionized water. Dissolve all raw materials in deionized water and stir until a uniform solution is obtained.

[0088] After 3 mL of catalyst was added to the mixed solution, the solution quickly gelled. After the obtained gel was dried at 120°C for 24 hours, the sample was transferred to a muffle furnace and heated to 220°C at a rate of 0.5°C / min for 2 hours to obtain a pretreated sample. The pretreated sample was crushed and ball milled in a ball mill at a ball-to-material ratio of 3:1 and a speed of 200r / min for 16 hours to obtain a composite powder of binder-wrapped reinforced particles.

[0089] The composite powder was poured into a mold, a pressure of 200 MPa was applied, and the mold was kept at 500 ° C for 2 hours for hot pressing to obtain a block green body. The green body was heated to 1100 ° C at a heating rate of 4 ° C / min in an argon environment and kept at this temperature for 2 hours to obtain a high-strength isotropic nanocrystalline / amorphous carbon block carbon material. Transmission electron microscopy images are shown in Figure 1 ; Its flexural strength is 133MPa, see Figure 4 Middle 1#.

[0090] Example 2

[0091] Ultra-high strength carbon (graphite) material is prepared by a two-step method, and the specific process is as follows:

[0092] (1) Preparation of reinforced particles:

[0093] Take 73.9g of acrylamide, 246.5g of fructose and 1.8g of N,N'-methylenebisacrylamide, and 677.8mL of deionized water. Dissolve all raw materials in deionized water and stir until a uniform transparent solution state. The solution was gelled at 80°C and dried for 24 hours to obtain a hydrogel. Subsequently, the hydrogel was heated to 220°C at a heating rate of 0.5°C / min in a muffle furnace at 220°C, and the pretreated product PG-220 was obtained after 2 hours of heat preservation. The PG-220 sample was heated to 900°C at 4°C / min in an argon environment and kept warm for 2 hours to obtain a carbonized product PG-900. The PG-900 sample was crushed and ball-milled in a ball mill at a ball-to-material ratio of 3:1 and a speed of 200r / min for 16 hours to obtain a reinforced particle carbonized powder.

[0094] (2) Preparation of ultra-high strength carbon (graphite) materials:

[0095] Prepare sufficient amounts of initiator (10% ammonium persulfate aqueous solution) and catalyst (10% triethanolamine aqueous solution) for use. Take 6g acrylamide, 20g fructose and 0.15g N,N'-methylenebisacrylamide, 1.5mL initiator, 41g reinforcing particles, and 55mL deionized water. Dissolve all raw materials in deionized water and stir until a uniform solution is obtained.

[0096] After 3 mL of catalyst was added to the mixed solution, the solution quickly gelled. After the obtained gel was dried at 120°C for 24 hours, the sample was transferred to a muffle furnace and heated to 220°C at a rate of 0.5°C / min for 2 hours to obtain a pretreated sample. The pretreated sample was crushed and ball milled in a ball mill at a ball-to-material ratio of 3:1 and a speed of 200r / min for 16 hours to obtain a composite powder of binder-wrapped reinforced particles.

[0097] The composite powder was poured into a mold, a pressure of 100 MPa was applied, and the mold was kept at 400 ° C for 2 hours for hot pressing to obtain a block green body. The green body was heated to 2400 ° C in an argon environment at a heating rate of 2 ° C / min and kept at this temperature for 3 hours to obtain a high-strength three-dimensional network graphene / amorphous carbon composite material. Transmission electron microscopy images are shown in Figure 2 ; Flexural strength is 111MPa, see Figure 4 Middle 2#.

[0098] Example 3

[0099] The present invention adopts a two-step method to prepare ultra-high strength carbon (graphite) material, and the specific process is as follows:

[0100] (1) Preparation of reinforced particles:

[0101] Take 73.9g of acrylamide, 246.5g of sucrose and 1.8g of N, N'-methylenebisacrylamide, and 677.8mL of deionized water. Dissolve all raw materials in deionized water and stir until a uniform transparent solution state. The solution was gelled at 80°C and dried for 24 hours to obtain a hydrogel. Subsequently, the hydrogel was heated to 220°C at a heating rate of 0.5°C / min in a muffle furnace at 220°C, and the pretreated product PG-220 was obtained after 2 hours of insulation. The PG-220 sample was heated to 1400°C at 4°C / min in an argon environment and kept warm for 2 hours to obtain a carbonized product PG-1400. The PG-1400 sample was crushed and ball-milled in a ball mill at a ball-to-material ratio of 3:1 and a speed of 200r / min for 16 hours to obtain a reinforced particle carbonized powder.

[0102] (2) Preparation of ultra-high strength carbon (graphite) materials:

[0103] Prepare sufficient amounts of initiator (10% ammonium persulfate aqueous solution) and catalyst (10% triethanolamine aqueous solution) for use. Take 6g acrylamide, 20g sucrose and 0.15g N,N'-methylenebisacrylamide, 1.5mL initiator, 41g reinforcing particles, and 55mL deionized water. Dissolve all raw materials in deionized water and stir until a uniform solution is obtained.

[0104] After 3 mL of catalyst was added to the mixed solution, the solution quickly gelled. After the obtained gel was dried at 120°C for 24 hours, the sample was transferred to a muffle furnace and heated to 220°C at a rate of 0.5°C / min for 2 hours to obtain a pretreated sample. The pretreated sample was crushed and ball milled in a ball mill at a ball-to-material ratio of 3:1 and a speed of 200r / min for 16 hours to obtain a composite powder of binder-wrapped reinforced particles.

[0105] The composite powder was poured into a mold, a pressure of 60 MPa was applied, and the mold was kept at 600 ° C for 2 hours for hot pressing to obtain a block green body. The green body was heated to 2800 ° C in an argon environment at a heating rate of 2 ° C / min and kept at this temperature for 3 hours to obtain a high-strength isotropic graphite material. Transmission electron microscopy images are shown in Figure 3 ; Flexural strength is 71MPa, see Figure 4 Middle 3#.

[0106] Comparative Example 1

[0107] This comparative example adopts the preparation process of CN 115849362A to prepare the carbon material, and the specific steps are:

[0108] (1) Step 1: preparing mixed solution, initiating gelation and preliminary dehydration:

[0109] Weigh 1.2 g of analytically pure N,N'-methylenebisacrylamide and put it into a beaker, add 90 g of deionized water, stir thoroughly to dissolve and clarify, slowly add 180 g of analytically pure glucose monohydrate while stirring in a 60°C water bath, dissolve until clarified, naturally cool to 40°C, slowly add 36 g of analytically pure acrylamide, and continue stirring until the solution is clarified to obtain a mixed solution; drop 0.6 g of a 10 wt% ascorbic acid aqueous solution and a 5 wt% hydrogen peroxide aqueous solution into the mixed solution, quickly stir evenly, pour into a mold, stand and wait for gelation, take out after the gel exotherm ends, obtain a hydrogel block, cut into pieces, put into an oven at 100°C for drying and dehydration for 48 hours, and obtain a xerogel;

[0110] (2) Step 2: Gel heat treatment and powder preparation:

[0111] A large amount of dry gel with free water removed is placed in the inner lining of the reactor, and analytical pure acetone is poured in to make the liquid level reach 2 / 3 of the volume. The lid is tightly covered and sealed in the outer lining. The sealed reactor is placed in an oven and the program is set to keep warm at 200°C for 8 hours. After the insulation is completed, it is cooled to room temperature. The block material in the reactor is taken out and the surface liquid is dried; the taken out block material is mechanically crushed to screen out particles below 20 mesh, and the particles are divided into two portions and poured into two planetary ball mills with a volume of 1L respectively, with a material-ball ratio of 1:1, of which the matching Zirconia ball milling beads occupy 1 / 3 of the volume, and the ball milling media are zirconia beads with particle sizes of 5mm, 10mm and 15mm. The mass ratio of 5mm, 10mm and 15mm zirconia beads is 5:3:2; the parameters of the planetary ball mill are set as follows: first run at a speed of 500r / min for 10min, then adjust to 360r / min and continue to run for 6h before shutting down, and the ground powder is passed through a 100-mesh sieve and sealed to prevent moisture. Finally, about 76g of powder raw material can be screened out from each jar.

[0112] (3) Step 3: Warm pressing, carbonization and graphitization:

[0113] 32 g of the prepared raw material powder was weighed and loaded into a Φ50 mm graphite mold for warm pressing. The temperature was slowly increased at a rate of 3°C / min and uniaxial pressurization was performed. The temperature was kept at 180°C, 220°C, 260°C and the highest temperature of 300°C for 30 minutes respectively, then the temperature was reduced to 220°C at a rate of 2°C / min and naturally cooled to room temperature to obtain a prefabricated body. The pressure reached a peak of 8 tons before keeping at 260°C, and slowly dropped to 6 tons before keeping at 300°C. No additional loading was performed during the cooling stage, and the temperature was unloaded when it dropped to below 200°C. After cooling to room temperature, the pressed body was taken out, and the mass of the body was about 27 g.

[0114] The pressed body is placed in an argon atmosphere tubular furnace at 1000°C for 1 hour to obtain a carbonized block, with a heating rate of 3°C / min and a cooling rate of 2°C / min. After cooling to 400°C, it can be cooled naturally. The carbonized block is then graphitized at 3000°C for 10 hours and finally cooled to room temperature to obtain a graphitized block, from a pressed block to a graphitized block.

[0115] The flexural strength of the carbon material prepared in Comparative Example 1 is 57 MPa.

[0116] By comparison, it can be clearly seen that the bending strength of the carbon material prepared in Comparative Example 1 is much lower than that in Example 1.

[0117] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing an ultra-high-strength carbon material, characterized in that: The following steps are involved: The reinforcing particles, acrylamide, water-soluble sugar, N,N'-methylenebisacrylamide, initiator and catalyst are added into deionized water and mixed evenly, and then dried, heat treated, crushed and ball milled in sequence to obtain composite powder; The composite powder is subjected to molding and carbonization treatment in sequence to obtain the ultra-high strength carbon material.

2. The method for preparing an ultra-high strength carbon material according to claim 1, characterized in that: Taking the sum of the weight percentages of the acrylamide, water-soluble sugar, N,N'-methylenebisacrylamide and deionized water as 100%, The mass fractions of the acrylamide, water-soluble sugar and N,N'-methylenebisacrylamide are 1-30%, 5-60% and 0.05-3% respectively, and the balance is water.

3. The method for preparing an ultra-high strength carbon material according to claim 1, characterized in that: The amount of the reinforcing particles added is 20% to 300% of the sum of the weight of the acrylamide, the water-soluble sugar, the N,N'-methylenebisacrylamide and the deionized water; and / or The initiator is an aqueous solution of ammonium persulfate with a mass concentration of 10%, and the amount added is 0.5%-3% of the total mass of the acrylamide, water-soluble sugar, N,N'-methylenebisacrylamide and deionized water; and / or The catalyst is a triethanolamine aqueous solution with a mass concentration of 10%, and the added amount thereof is 0.5%-3% of the total mass of the acrylamide, water-soluble sugar, N,N'-methylenebisacrylamide and deionized water.

4. The method for preparing an ultra-high strength carbon material according to claim 1, characterized in that: The preparation process of the enhanced particles is as follows: acrylamide, water-soluble sugar and N,N'-methylenebisacrylamide are mixed and dissolved in deionized water, stirred to form a uniform solution; and then dried to obtain a hydrogel; The hydrogel is subjected to heat treatment to obtain a pre-treated product; Carrying out a carbonization treatment on the pretreated product under an inert atmosphere to obtain a carbonized product; The carbonized product is crushed and ball-milled to obtain reinforced particles.

5. The method for preparing an ultra-high strength carbon material according to claim 4, characterized in that: Calculated by weight percentage, the mass fractions of acrylamide, water-soluble sugar and N,N'-methylenebisacrylamide are 1-30%, 5-60% and 0.05-3% respectively, and the balance is deionized water.

6. The method for preparing an ultra-high strength carbon material according to claim 4, characterized in that: The conditions during the heat treatment are: heating to 140-350°C at a heating rate of 0.1-20°C / min, and then keeping at this temperature for 0.5-30h; and / or The conditions during the carbonization treatment are: heating to 500-1600°C at a heating rate of 1-20°C / min, and then keeping at this temperature for 0.5-30h; and / or The conditions during the ball milling process are: ball-to-material ratio 1-20:1, ball milling speed 100-600r / min, and ball milling time 6-48h.

7. The method for preparing an ultra-high strength carbon material according to claim 1, characterized in that: The conditions in the molding process are: Keep warm for 0.5-6h at a pressure of 10-600MPa and a temperature of 120-900℃.

8. The method for preparing an ultra-high strength carbon material according to claim 1, characterized in that: The conditions of the carbonization process are: In an inert atmosphere, the temperature is raised to 1000-3000°C at a heating rate of 1-20°C / min, and then kept at this temperature for 0.5-24 hours.

9. The method for preparing an ultra-high strength carbon material according to claim 8, characterized in that: During the carbonization process, when the temperature is raised to 1000-1600° C., a high-strength isotropic nanocrystalline / amorphous carbon bulk carbon material is obtained; When the temperature is raised to 1800-2400°C, a high-strength isotropic three-dimensional network graphene / amorphous carbon block carbon material is obtained; When the temperature is raised to 2600-3000°C, a high-strength isotropic graphite material is obtained.

10. An ultra-high strength carbon material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for fixing carbon in saccharides and preparing high-purity carbon (graphite) material

    CN104176725A

  • High-strength carbon foam (CF) material and preparation method thereof

    CN106698415A

  • One-dimensional and two-dimensional biochar synergistically enhanced carbon aerogel material as well as preparation method and application thereof

    CN114380285A

  • Preparation method of block carbon / graphite material based on saccharide small molecules

    CN115849362A

  • High-purity carbon material and preparation method thereof

    CN115974047A